Análisis de la evolución de la Balanza de Pagos del Ecuador en el periodo 2010-2015 - Yangua Conde, Lilian Camila (2016)
This research work shows in detail the evolution that has taken the Balance of Payments of Ecuador during the period 2010-2015; first through the study of each of the accounts that make it up, so that the level of contribution that the different economic sectors on it, alongside the factors that influence the behavior of the results are determined is identified He presented the external sector of the Ecuadorian economy during the analysis period, hence the proposal aimed at consolidating this macroeconomic indicator considered strategies. The research uses a historical approach, through the methodology of documentary qualitative character, ie, descriptive with the collection and subsequent analysis of the information obtained, the main sources were documents issued by relevant agencies, as studies by experts in the field. The results show that the current account has presented a steady deficit situation mainly given by the limited export supply held by the Ecuador, which also is directly related to the production structure that characterizes the country. Thus, it is evident that the economic sectors that have largely contributed to the composition of the balance of payments were two: the primary and secondary, since they are raw materials and manufactured products which are intended for trade. In the same context and following up on the factors affecting the behavior of the balance of payments, the fact that Ecuador is a dollarized economy has increased the level of vulnerability to events occurring abroad; in the same way, the lack of competitiveness in goods and services for the international market is another important that the results presented in relation to foreign trade are deficient element. Based on the above, they raised strategies to improve the position of Ecuador in the international context, based on principles and priorities that are intended to achieve economic and social welfare of the population.